The Stabilizing Effect of Magnetic Field for the Shape of Yeast Cells Saccharomyces cerevisiae on Silicon Surface - Olena Nizhelska; Lolita Marynchenko; Volodymyr Makara; Svitlana Naumenko; Alla Kurylyuk (Innovative Biosystems and Bioengineering, 2018)
Background. Development of methods of the targeted delivery of drugs in the nanocarriers with magnetic nanomaterials under the control of the magnetic field, industrial application of magnetically sensitive yeast, study of the viability and preservation of the biological activity of immobilized cells and the influence of various factors on the stabilization of these systems.